2002
DOI: 10.1002/er.839
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a vertical ground-source heat pump system in Izmir, Turkey

Abstract: SUMMARYThis study summarizes the cooling performance of a ground-source heat pump system which was installed in a 65-m 2 room in the Solar Energy Institute, Ege University, Izmir (568 degree-days cooling, base: 228C; 1226 degree-days heating, base: 188C) Turkey. The institute, built in 1986, has a liveable floor area of 3000 m 2 , and uses passive solar techniques. The heating and cooling loads of the room were, respectively, 3.8 and 4.2 kW at design conditions. The system was commissioned in May 2000 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Hepbas¸lı [18] has reported that COP r values are in the range of 3.52-4.92 for commercially available systems according to the U.S. Department of Energy (U.S.D.O.E.). In Canada, earth energy systems have COP between 2.5 and 3.8 [42].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hepbas¸lı [18] has reported that COP r values are in the range of 3.52-4.92 for commercially available systems according to the U.S. Department of Energy (U.S.D.O.E.). In Canada, earth energy systems have COP between 2.5 and 3.8 [42].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, greater efficiencies can be attained variable speed GSHP instead of single speed one [44]. GSHP is a relatively new technology for Turkey and along with improved system design suggestions as discussed by Hepbaslı [18] and Kavanaugh et al [44], new grouting materials, piping and manifolds with reduced pressure drop, etc., the annual performance factor of GSHP can also be optimized in Turkey. Sanner and Kohlsch [4] have reported that COP of heat pumps for GSHP systems increases linearly with increasing number of tested heat pumps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, many studies have focused on efficiency enhancement and performance evaluations of various GHP systems [2][3][4][5]. Accordingly, studies of GHP are in progress from many worldwide perspectives.…”
Section: Introductionmentioning
confidence: 99%